Network analysis integrating social network theory, method, and application with R - Rawlings, Craig M.; Smith, Jeffrey A. 1962-; Moody, James ca. 20./21. Jh; McFarland, Daniel A. (Cambridge University Press, 2023)
"For both students and professionals seeking to understand the burgeoning field of network analysis, our text offers a comprehensive overview that integrates theory, method, and cutting-edge application with R (a free platform that is becoming the standard for the field)"--
Keywords: Methodologie; Netzwerkanalyse -- Soziologie; Forschungsmethode; Social sciences / Network analysis; Social networks / Research / Methodology; Application software; Web applications